2001
DOI: 10.1029/01eo00330
|View full text |Cite
|
Sign up to set email alerts
|

Seismic waves generated by aircraft impacts and building collapses at World Trade Center, New York City

Abstract: Seismologists sometimes do their work of data acquisition and analysis against a tragic background. Usually the context is fieldwork far from home, in an area subjected to the natural but sometimes devastating effects of an earthquake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…For the aforementioned observations, the structures were excited by internal or external forces applied at the top, and the wave diffracted into the soil was easily identifiable on the recording stations. This is not a local phenomenon, because Kanamori et al (1991), Favela et al (2002), and Kim et al (2001) have observed ISSI at distances of over 50 km. These observations have been confirmed by simplified 2D numerical modeling (Wirgin and Bard, 1996) and generalized to a building cluster simulating a city (Kham et al, 2006, Isbiliroglu et al, 2015, reproducing, in some cases, the unusually long and monochromatic waves observed in Mexico City in 1985 (Singh et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the aforementioned observations, the structures were excited by internal or external forces applied at the top, and the wave diffracted into the soil was easily identifiable on the recording stations. This is not a local phenomenon, because Kanamori et al (1991), Favela et al (2002), and Kim et al (2001) have observed ISSI at distances of over 50 km. These observations have been confirmed by simplified 2D numerical modeling (Wirgin and Bard, 1996) and generalized to a building cluster simulating a city (Kham et al, 2006, Isbiliroglu et al, 2015, reproducing, in some cases, the unusually long and monochromatic waves observed in Mexico City in 1985 (Singh et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…This effect is exacerbated in the presence of a strong impedance contrast between the soil and the foundations. On the other hand, Jennings (1970), Kanamori et al (1991), Gué-guen et al (2000), Cornou et al (2004), and Kim et al (2001) identified waves in seismic ground motions recorded in urban areas or close to buildings. These waves are generated by structure vibrations, due to inertial soil-structure interaction (ISSI).…”
Section: Introductionmentioning
confidence: 99%
“…In a third attempt, the terrorists lost control over their hijacked aircraft, and crashed in the Pennsylvania countryside. These air crashes were well recorded by stations being part of the New England seismograph network, and analysis results have been published [1].…”
Section: September 11 Th 2001 Terrorist Attacks On New York and Wasmentioning
confidence: 99%
“…Advanced methods are used to track and locate almost any source, which emits seismic recordable signals in the Earth's crust. Following the September 11 th , 2001 terrorist attack on the WTC towers in New York and on the Pentagon in Washington DC, the accurate timing of impacts and of building collapses were determined by analysis of registrations at nearby seismograph stations [1]. The accidental sinking of the nuclear submarine Kursk in the Barents Sea was Registered at Fennoscandian stations, and was initially reported as such [2].…”
Section: Introductionmentioning
confidence: 99%
“…• The September 11 attacks on the World Trade Center were recorded and confirmed by seismic sensors outside of New York City (Kim et al 2001); there were no seismic sensors inside the city. The timeline of the events, including the impacts into both towers and their subsequent collapse, were recorded on seismic sensors 34 km from Ground Zero.…”
Section: Introductionmentioning
confidence: 99%